The Traditional Chinese Medicine "Hu-Qian-Wan" Attenuates Osteoarthritis-Induced Signs and Symptoms in an Experimental Rat Model of Knee Osteoarthritis. (9th February 2022) - Hou, Pu-Wei; Liu, Shan-Chi; Tsay, Gregory J.; Tang, Chih-Hsin; Chang, Hen-Hong
Abstract : Background . Knee osteoarthritis (KOA) is a chronic, low-grade inflammatory disease that affects knee joints and causes functional disability in the elderly. KOA is typically treated with oral NSAIDs, which are commonly associated with gastrointestinal side effects or cardiovascular complications. Traditional Chinese medicine (TCM) is widely used by patients with KOA in Taiwan; the Hu-Qian-Wan (HQW) formula is typically prescribed. We investigated the therapeutic role of a modified version of the HQW decoction in Sprague-Dawley rats with KOA induced by anterior cruciate ligament transection (ACLT) of the right knee. Materials and Methods . Thirty rats were randomly assigned to five groups (six animals each): arthrotomy alone (sham surgery, controls), ACLT only, ACLT + low-dose (1, 000 mg/kg) HQW, ACLT + high-dose (3, 000 mg/kg) HQW, and ACLT + celecoxib (30 mg/kg). All study groups underwent weight-bearing behavioral testing, micro-computed tomography (CT), and histological examinations of the knee joint cartilage, as well as immunohistochemical analyses of levels of interleukin (IL) 1 β and tumor necrosis factor (TNF) α expression in articular cartilage. Results . At 6 weeks, compared with ACLT group only, ACLT rats administered high-dose HQW or celecoxib exhibited the fewest weight-bearing deficits, the greatest improvements from baseline in articular cartilage architecture, and the lowest amounts of TNF- α and IL-1 β staining in cartilage and synovial sections (all values were significant compared with the ACLT-only group). The only values that were significantly increased by ACLT + low-dose HQW compared with ACLT alone were bone mineral density and trabecular numbers. Conclusion . Our findings suggest that high-dose HQW improves weight-bearing asymmetry, decreases bone loss, and reduces levels of TNF- α and IL-1 β in the affected joint in ACLT-induced KOA rats. More evidence is needed to support our findings.